Assessing the role of organic food supply chain traceability on food safety and consumer wellbeing: A mediated-moderation investigation - Guanqi, Zhou; Husnain, Mudassir (Frontiers in Psychology, 2022)
Drawing on dynamic capabilities theory, this study offers a comprehensive framework for examining the relationships between organic food supply chain traceability, consumer wellbeing, and food safety trust based in organic food sector. The study also explores how consumer awareness of organic food influences the relationship between consumer wellbeing and food safety. We also look at a mediated moderation mechanism in the relationships stated earlier. Using a survey as the primary data collecting method, a total of 221 usable responses were collected. To test the hypothesized relationships between all variables, SPSS PROCESS Macro 3.3 is utilized. The findings show that the organic food traceability OFSC affect food safety trust and food safety and consumer wellbeing are positively associated, while consumer awareness of organic food acts as a moderator on the relationship between food safety trust and consumer wellbeing. Also consumer awareness conditionally influences the strength of the indirect relationship between OFST and consumer wellbeing via food safety, thereby indicates a mediated moderation mechanism among the study variables. This study clarifies how consumer food safety trust and organic food traceability can enhance their wellbeing. It contributes to the theory of dynamic capabilities as well as organic traceable product marketing strategies.